Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/app.47490
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic acid)–thermoplastic starch–cotton composites: Starch‐compatibilizing effects and composite biodegradability

Abstract: Poly(lactic acid) (PLA) is a biodegradable, brittle, and high-cost polymer, which can be applied over structural components and green packaging. In this study, we reinforced PLA with natural cotton (10 wt %) and thermoplastic starch (TPS; 3 wt %) to obtain a biodegradable and lower cost composite. TPS was incorporated in three distinct ways: it was blended, coated, and blended and coated. In this study, we investigated the compatibilization of TPS in the improvement of matrix-reinforcement adhesion and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The positive effect of starch on the properties of other composites of polymer with cellulose has also been reported but it is seldomly explicitly mentioned as a compatibilizing effect except in PLA. 32,33 Several studies have demonstrated that using tert-butanol (TB) as a freeze-drying medium during the production of cellulose nano-fibers or nano-crystals prevents their aggregation [34][35][36][37][38] but seldomly to produce composites. Petersson et al 39 studied composites based on PLA and cellulose nanocrystals prepared by solution casting.…”
Section: Introductionmentioning
confidence: 99%
“…The positive effect of starch on the properties of other composites of polymer with cellulose has also been reported but it is seldomly explicitly mentioned as a compatibilizing effect except in PLA. 32,33 Several studies have demonstrated that using tert-butanol (TB) as a freeze-drying medium during the production of cellulose nano-fibers or nano-crystals prevents their aggregation [34][35][36][37][38] but seldomly to produce composites. Petersson et al 39 studied composites based on PLA and cellulose nanocrystals prepared by solution casting.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the PLA/PBAT blend systems have been tested as materials intended for the production of films, injection molding or three-dimensional (3D) printing. The production of composite laminates based on PLA resin has not been the subject of intensive research, so far, but the appearance of this type of materials on the market indicates an interesting trend in the use of biopolymers The use of PLA as a matrix for composites and laminates was already investigated in case of ramie fibers [ 60 , 61 ], bamboo [ 62 , 63 ], cotton [ 64 , 65 , 66 ], kenaf [ 67 ] or flax [ 26 , 68 , 69 , 70 ]. The use of flax fiber (FF) reinforcement was for us the most promising concept, since the reinforcing efficiency for already investigated PLA/FF composite systems was very high, which was confirmed in many studies [ 68 , 71 , 72 , 73 , 74 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reviews on PLA (Macedo et al; 6 Farah et al; 7 Castro‐Aguirre et al 8 ) included processing techniques and applications, degradation pathways, end‐of‐life scenarios for PLA products, and its environmental footprint. According to these reviews, the PLA's biodegradation depends on several parameters and can take weeks to months.…”
Section: Introductionmentioning
confidence: 99%
“…PLA's disadvantage is its high cost compared to conventional polymers, but blends with low‐cost biodegradable materials become PLA‐based composites economically viable and improve biodegradability 1,6 . The application of lignocellulosic fibers as reinforcement has been widely studied because they have low density and low abrasiveness and can be incorporated in high levels reducing cost since most of them are agro‐industrial residues from sugarcane, cassava, wood, and coir 9–13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation